"Not for Human Consumption": A Review of Emerging Designer Drugs. Issue 7 (8th April 2014) - Musselman, Megan E.; Hampton, Jeremy P.
<x xml:space="preserve">Abstract</x> Synthetic, or "designer" drugs, are created by manipulating the chemical structures of other psychoactive drugs so that the resulting product is structurally similar but not identical to illegal psychoactive drugs. Originally developed in the 1960s as a way to evade existing drug laws, the use of designer drugs has increased dramatically over the past few years. These drugs are deceptively packaged as "research chemicals, " "incense, " "bath salts, " or "plant food, " among other names, with labels that may contain warnings such as "not for human consumption" or "not for sale to minors." The clinical effects of most new designer drugs can be described as either hallucinogenic, stimulant, or opioid‐like. They may also have a combination of these effects due to designer side‐chain substitutions. The easy accessibility and rapid emergence of new designer drugs have created challenges for health care providers when treating patients presenting with acute toxicity from these substances, many of which can produce significant and/or life‐threatening adverse effects. Moreover, the health care provider has no way to verify the contents and/or potency of the agent ingested because it can vary between packages and distributors. Therefore, a thorough knowledge of the available designer drugs, common signs and symptoms of toxicity associated with these agents, and potential effective treatment modalities are essential to appropriately manage these patients.